FOUNDATION OF RESTORATION – PIN RETAINED AMALGAM (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Dental amalgam has served as an excellent and versatile restorative material for many years. There is still no adequate economic alternative for dental amalgam. Pins are used whenever adequate resistance and retention forms cannot be established with slots.locks and other undercuts only. It is an important adjunt in the restoration of extensive carious teeth. Pins not only helps in binding of amalgam to the tooth but also binds weak tooth structure to the amlgam. This case report present the innovative technique that outlines the reconstruction of severely damaged posterior teeth with missing functional cusp.